The Impact of Renewable and Non-renewable Energy on Carbon Dioxide Emission: An Empirical Analysis for Euro Mediterranean Countries - Al Araby, Lamess; Samak, Nagwa; Ibrahiem, Dalia M. (International Journal of Energy Economics and Policy, 2019)
Given that carbon dioxide emissions is the main reason of environmental pollution and global warming, this paper attempts to investigate the impact of gross domestic product (GDP) per capita, electricity production from different sources (including renewable and non-renewable energy) and industrial sector share in GDP on Carbon dioxide emissions (CO2) for a Euro Mediterranean panel of 25 countries using dynamic panel data model for the period 2002-2016. The paper uses the Hausman test and panel unit root test in order to verify the stationary of the variables series employed. Generalized least square estimator is used for building Panel regression model. The results indicate a significant positive impact of economic growth and electricity output from coal on CO2 emissions In contrast, renewable resources have a negative impact on CO2 emission. Keywords: Caron Dioxide Emissions, Renewable Energy, Euro Mediterranean JEL Classifications: C23, O13, P18, P28, P48, Q42 DOI: https://doi.org/10.32479/ijeep.8254